Les exilés italiens et l’anti-machiavélisme français au XVIe siècle - Paolo Carta (Laboratoire Italien, 2002)
The author investigates the Huguenot anti-Machiavellian works composed by the Italian republicans exiles in France during the 16th century. The relationships between Italian exiles are here studied from the vantage of the unpublished correspondence of Jacopo Corbinelli, a Florentine man of letters who lived under the protection of Catherine of Medici, becoming first the preceptor of Francis, Duke of Alençon, and then the instructor of Henry III.